2005
DOI: 10.1016/j.molcel.2005.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Recombination at Collapsed Replication Forks: the Payoff for Survival

Abstract: Recombination is believed to assist replication when forks collapse. By using an elegant system, Lambert et al. (2005) address the consequences of recombination at blocked forks. They show that chromosomal rearrangements are the price to pay for cell viability when forks collapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
3
1
Order By: Relevance
“…With regard to DNA double strand breaks, we found that only approximately 14% of MCF7 and 9% of NDHF freeze-thawed cells exhibited an enhanced number of γH2AX/53BP1 foci, which is in contrast to numerous studies 42 44 , 46 48 . Importantly, these cells contained a minimum of 30 γH2AX/53BP1 foci/nucleus, but they typically had more than 100.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…With regard to DNA double strand breaks, we found that only approximately 14% of MCF7 and 9% of NDHF freeze-thawed cells exhibited an enhanced number of γH2AX/53BP1 foci, which is in contrast to numerous studies 42 44 , 46 48 . Importantly, these cells contained a minimum of 30 γH2AX/53BP1 foci/nucleus, but they typically had more than 100.…”
Section: Discussioncontrasting
confidence: 70%
“…The literature provides differing conclusions regarding cell survival upon extensive replication fork damage 42 44 , 46 48 ; therefore, it is difficult to predict the fate of freeze-thawed cells affected by this damage, particularly if the cells suffer from additional types of chromatin alterations. For instance, Dixon and colleagues described 56 impaired DNA damage signaling and repair in cells exposed to hyperosmolar microenvironments, which caused chromatin condensation.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of checkpoint proteins, such as the Mec1 kinase, stalling replication forks can lead to disengagement of the replisome, resulting in fork collapse along with the formation of DSBs (Lopes et al, 2001;Tercero and Diffley, 2001;Sogo et al, 2002;Pellicioli and Foiani, 2005;Trenz et al, 2006). To determine if the absence of the checkpoint protein Mec1 would trigger an elevated recruitment of HR proteins to DNA replication forks, cells were analyzed for Rad54 foci in the presence or absence of SRS2 in a mec1∆ strain where SML1 was also deleted in order to suppress mec1∆ lethality.…”
Section: Recombination Foci Accumulate In the Absence Of Srs2 Activitymentioning
confidence: 99%
“…The EM result provides an alternative (but not mutually exclusive) model. Many studies of site-specific replication fork barriers have shown that a stalled fork is subject to breakage and elevated recombination (see (62,84) for review).…”
Section: Consequences Of Fork Stalling and Chromosome Breakagementioning
confidence: 99%